PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS PUISI KELAS VIII DI SMP NEGERI 12 SINGKAWANG - Yudea Helnanda; Eti Sunarsih; Zulfahita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the background of students' low ability to write poetry. This is due to the fact that many students experience difficulties in learning to learn, low levels of student vocabulary, lack of students' understanding of poetry structure, and lack of students' imagination and creativity. This research is focused on poetry writing materials using the discovery learning model. The formulation of the problem in this study is whether there is a difference in improvement, how the discovery learning model is implemented, and how students respond after the application of the discovery learning model. The purpose of this study is to find out the difference in improvement, to find out the implementation of the discovery learning model, to find out the students' response after the application of the discovery learning model. The method used in this study is an experimental method. The form of quantitative research and design is a nonequivalent control group desaign. The instruments used were a test sheet for writing poetry, an implementation observation sheet, and a student response questionnaire sheet. The research data was processed quantitatively. This implementation was carried out in the second cycle with the second meeting and using II classes. Each cycle consists of planning, execution, observation, and reflection. The achievement of previous student learning outcomes in poetry writing skills only reached 53.70%. After getting the action in the first cycle, the percentage of completeness was 28.1%. There was an increase in the second cycle, which was 69.3%. Thus, learning to write poetry using this discovery learning model is very suitable for the characteristics of junior high school students, therefore, discovery learning should be used regularly in learning.